Seismic vulnerability assessment of confined masonry structures by macro-modeling approach. (October 2020) - Ahmed, Asfandyar; Shahzada, Khan
Abstract: As seen during numerous earthquakes, confined masonry exhibited a reliable anti-seismic response due to a number of factors. To understand the effect of these factors, a case study of full scale confined masonry (CM) structure is considered and results of its numerical assessment are described. It focus mainly on the evaluation of factors such as masonry strength, wall density, pre-compression level and properties of the confining elements. The numerical study is performed using advanced numerical simulations in ATENA environment. A rigorous analysis of the nonlinear behavior of CM structures involves advanced nonlinear finite element models and a stable computational cost, making these procedures inappropriate for everyday applications. Therefore, in recent times, several researchers have offered simplified methodologies. In this study a macro-element simplified model based on smeared crack and total stress–strain models is applied to a benchmark CM prototype structure. Results are presented as force–displacement curves, types of failure modes, ductility and damage index. From the parametric studies it was revealed that material strength play a central role on the behavior of confined masonry subjected to lateral loading and determine the effect of other parameters such as pre-compression level, wall density and properties of confining elements.